2011
DOI: 10.1111/j.1745-4514.2010.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Phenolic Content of Flour and Protein Concentrate of Amaranthus Cruentus Seeds

Abstract: The aim of this work was to investigate bioactive compounds and antioxidant activity in flour (FAc) and protein concentrate (PCAc) from Amaranthus cruentus seeds (Ac), and to study their effect on the liver histoarchitecture of Wistar rats.Total phenols (mg gallic acid eq/100 g dry weight) content was 73.78 Ϯ 1.70 for FAc, and 190.23 Ϯ 1.50 for PCAc. The antioxidant activity was estimated by: 1,1-diphenyl-2-picrylhydrazyl (DPPH), nitric oxide scavenging activity (NO) and b-carotene bleaching method (b-carotene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
(28 reference statements)
2
25
0
1
Order By: Relevance
“…In the present work, we aimed to delve further into the effects of salt treatment on the seed proteome and on the polyphenol content, and AA of seed extracts. The PC of Amaranthus cruentus seeds were reported to have improved nutritional quality as compared with flour through increased content of factors that directly or indirectly influence lipid metabolism and enhance antioxidant protection (Escudero et al, 2011 ). The AA of PCs obtained through different pilot-scale industrial processes from A. mantegazzianus seeds was recently evaluated in order to optimize production for the food industry (Castel et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, we aimed to delve further into the effects of salt treatment on the seed proteome and on the polyphenol content, and AA of seed extracts. The PC of Amaranthus cruentus seeds were reported to have improved nutritional quality as compared with flour through increased content of factors that directly or indirectly influence lipid metabolism and enhance antioxidant protection (Escudero et al, 2011 ). The AA of PCs obtained through different pilot-scale industrial processes from A. mantegazzianus seeds was recently evaluated in order to optimize production for the food industry (Castel et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increased total polyphenolics content (TPC) and antioxidant activity (AA) in methanol extracts of quinoa seeds harvested from plants grown under salinity has been observed, suggesting that stressful conditions may positively affect the seed's content of these important bioactive compounds (Ruiz et al, 2016a ). Flour and the protein concentrate (PC) of seeds of amaranth, a close relative of quinoa, have been shown to contain polyphenols and to possess AA (Escudero et al, 2011 ). To date, these parameters have not been investigated in quinoa protein extracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of methanolic extract of A. spinosus significantly increased the protein and glycogen contents in liver of Sprague Dawley rats thus indicating it to be safe for treatment of liver problems [55]. Escudero et al [56] based on their observations of lipid profile and liver histoarchitecture in Wistar rats, concluded that presence of phenols in flour and protein concentrate of A. cruentus seeds provokes an increase in antioxidant defenses, thus playing a protective role in liver. A. hypochondriacus seed feed significantly increased activity and gene expression of Cu, Zn-SOD; decreased activity of aspartate aminotransferase (SGOT) and content of malondialdehyde (MDA) (p < 0.001) in serum; decreased NADPH oxidase transcript levels (p < 0.05) in liver, suggesting its protective effect in rats intoxicated with ethanol [57].…”
Section: Hepatoprotectivementioning
confidence: 99%
“…Grain amaranth has been shown to exhibit antioxidant activity and this has been attributed to its content of polyphenols, anthocyanins, flavonoids, and tocopherols (Klimczak et al 2002;Escudero et al 2011). Phenolic content of grain amaranth varies between species and may be affected by environmental conditions .…”
Section: Introductionmentioning
confidence: 99%